Guideline for sustainable management of wetlands in Ihemi cluster - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2016)
The government of Tanzania is highly concerned with management of wetland hence it is fully committed to ensure that they are sustainably managed. In Tanzania, the wetlands are known to be nature’s water store on land which supports a number of sectors including agriculture, livestock, forest and wildlife providing vital ecosystems support. In general, wetlands in the Ihemi Cluster face a number of challenges which some of them affects the ecosystem and livelihood of communities. Agriculture being the major economic activity conducted in Ihemi Cluster has modulated the wetland, hence a guideline for sustainable management of the wetlands needs to be developed and implemented. Therefore this guideline provides an approach for enhancing management of wetlands sustainably for the present and future generations in the Ihemi Cluster.